Speech-Language Pathology and Audiology in South Africa: Clinical Training and Service in the Era of COVID-19 - Katijah Khoza-Shangase; Nomfundo Moroe; Joanne Neille (International Journal of Telerehabilitation)
Introduction and purpose: The novel coronavirus (COVID-19) presented new and unanticipated challenges to the provision of clinical services, from student training to the care of patients with speech-language and hearing (SLH) disorders. Prompt changes in information and communication technologies (ICT), were required to ensure that clinical training continued to meet the Health Professions Council of South Africa’s regulations and patients received effective clinical care. The purpose of this study was to investigate online clinical training and supervision to inform current and future training and clinical care provision in SLH professions. Methodology: A scoping review was conducted using the Arksey and O'Malley (2005) framework. The electronic bibliographic databases Science Direct, PubMed, Scopus, MEDLINE, and ProQuest were searched to identify publications about online clinical training and supervision and their impact on clinical service during COVID-19. Selection and analysis were performed by three independent reviewers using pretested forms. Results and Conclusions: The findings revealed important benefits of teletraining and telepractice with potential application to South African clinical training and service provision. Five themes emerged: (1) practice produces favorable outcomes, (2) appreciation for hybrid models of training and service delivery, (3) cost effectiveness is a “big win” (4) internationalization of remote clinical training and service provision, and (5) comparable modality outcomes. These findings may have significant implications for teletraining and telepractice in low-and-middle income countries (LMICs) in the COVID-19 era and beyond, wherein demand versus capacity challenges (e.g., in human resources) persist. Current findings highlight the need for SLH training programmes to foster a hybrid clinical training model.  Few studies were conducted in LMICs, indicating a gap in such research.